1991
DOI: 10.2307/2136798
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Health Risks and Physical Symptoms Among the Homeless

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Concerning the type of symptoms, women reported more erythema nodosum, starting problems, fatigue, arthralgia, chest and abdominal pain. These results are consistent with trends in the general population that women report more symptoms (Ritchey et al, 1991) and are more emotionally expressive (Edwards, Nazroo & Brown, 1998). It is tempting to speculate that men and women cope differently with symptoms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Concerning the type of symptoms, women reported more erythema nodosum, starting problems, fatigue, arthralgia, chest and abdominal pain. These results are consistent with trends in the general population that women report more symptoms (Ritchey et al, 1991) and are more emotionally expressive (Edwards, Nazroo & Brown, 1998). It is tempting to speculate that men and women cope differently with symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…Whilst Sherrill, Lebowitz, Knudson, and Burrows (1993) and Janson-Bjerklie, Carrieri, and Hudes (1986) reported gender differences in disease symptoms, Van den Boom et al (1998) found no such differences between COPD patients who did or did not consult their general practitioners concerning respiratory symptoms. Moreover, gender differences were also found in married people (Mookherjee, 1997), homeless people (Ritchey, La Gory, & Mullis, 1991) and with regard to sensitive cough reflex, in healthy subjects (Dicpinigaitis & Rauf, 1998).…”
Section: Introductionmentioning
confidence: 82%
“…Many described the health status of a local homeless population, 14,21,5160 whereas others examined health behaviors or health risks. 61–63 Although the search strategy targeted studies that included the prevalence of hypertension or diabetes, some studies had broad health foci, and others focused on specific conditions. 64–67 Two studies examined the nutritional status of the diets of homeless individuals.…”
Section: Resultsmentioning
confidence: 99%
“…This instrument has robust psychometric properties (Pearlin & Schooler, 1978) and several studies have demonstrated its validity with homeless adults and those who have psychiatric diagnoses or disabilities (Badger, 2001;Blankertz, 2001;Marshall, Burnam, Koegel, Sullivan, & Benjamin, 1996;Ritchey, La Gory, & Mullis, 1991;Rosenfield, 1992;Shern et al, 2000). In this research, internal consistency coefficients were acceptable ranging from .71 to .73.…”
Section: Masterymentioning
confidence: 99%